Aggregation of indistinguishability operators. - Bejines-López, Carlos; Ardanza Trevijano, Sergio; Chasco Ugarte, María Jesús; Elorza, Jorge (Elsevier, 2021)
The paper studies the aggregation of pairs of T-indistinguishability operators. More concretely we address the question whether is a T-indistinguishability operator if are T-indistinguishability operators. The answer depends on the aggregation function, the t-norm T, and the chosen T-indistinguishability operators. It is well-known that an aggregation function preserves T-transitive relations if and only if it dominates the t-norm T. We show the important role of the minimum t-norm in this preservation problem. In particular we develop weaker forms of domination that are used to provide characterizations of -indistinguishability preservation under aggregation. We also prove that the existence of a single strictly monotone aggregation that satisfies the indistinguishability operator preservation property guarantees all aggregations to have the same preservation property.
Keywords: Conjuntos difusos; Aggregation; Fuzzy sets